AREA DEVELOPMENT PLAN TOD/TRANSIT ORIENTED DEVELOPMENT AT LRT CIBUBUR STATION - Akbar, Iyus Sidik (Universitas Ibn Khaldun Bogor, 2021)
Cibubur LRT Station is an LRT Station in Depok City which is located on Taman Bunga street, Harjamukti, Cimanggis district, Depok City, West Java 16454, to be precise next to the Jagorawi toll road. The concept of Transit Oriented Development (TOD) is a spatial engineering approach that focuses its development around transit points. The space developed in a transit-oriented area has the characteristics of high density, various mixes (updates) and a design area that is friendly to pedestrians and bicycle users. The purpose of this study was to analyze the designation of mixed land according to the roles and functions of the TOD and to predict the amount of generated traffic pull from and to the TOD area development location. In knowing the land use of the TOD transit area at the Cibubur LRT station, it was carried out by means of an analysis of the designation of the main and supporting functions of the TOD, after data output was already there compared to the standard transit node, with standard pedestrian facilities, TOD standard from ITDP and to analyze the generation and pulls in the TOD Cibubur area using the ITE-9th table. The results of the KDB value obtained throughout the building are 70% of the maximum land cover (Land Converage) TOD of the city service sub-center of 70% which is contained in the technical criteria for TOD development based on the type of TOD and the total KDB figure is 5.00 from a maximum number of 3.0 to 5.0. and for the generated value obtained in the land use of the TOD Cibubur area of 20,987 trips / hour in the morning (AM), and at night of 38,498 trips / hour.